Football injuries during FIFA tournaments and the Olympic Games, 1998-2001 - Junge, A.; Dvorak, J.; Graf-Baumann, T.; Peterson, L. (The American Journal of Sports Medicine, 2004)
BACKGROUND: Standardized assessment of sports injuries provides not only important epidemiological information, but also directions for injury prevention, and the opportunity for monitoring long-term changes in the frequency and characteristics of injury. PURPOSE: Development and implementation of an easy to use injury-reporting system to analyze the incidence, circumstances and characteristics of injury during major international football tournaments. STUDY DESIGN: Prospective survey. METHODS: A comprehensive injury report form was developed, and implemented during 12 international football tournaments. The physicians of all participating teams were asked to report all injuries after each match. The response rate was 84% on average. RESULTS: A total of 901 injuries were reported from 334 matches, which is equivalent to an incidence of 2.7 injuries per match. Approximately one injury per match resulted in a player's absence from training or matches. On average 86% of the injuries arose as a result of contact with another player, and approximately half of all injuries were caused by foul play. The number of injuries per match differed substantially between the tournaments for players of different age, sex and skill-level. CONCLUSION: An injury-reporting system has been implemented as matter of routine in FIFA tournaments. The consistent findings in the present study demonstrate the high quality of the data obtained.